Opportunities for Indian women in gig jobs without using digital platforms - Santra, Sayantani (Managing global transitions, 2025)
Flexible working hours can provide a better option for Indian women entering the workforce. This can be accomplished by engaging in gig jobs without depending on a digital platform, as many individuals have limited access to technology. Casual labourers and self-employed workers are considered gig workers who can perform their jobs without utilising digital platforms. The Probit model identifies the factors that can enhance the likelihood of such gig jobs occurring without the use of a digital platform for Indian women. By employing a Bivariate Probit regression model based on Periodic Labour Force Survey data for 2022–23 and addressing endogeneity, the paper demonstrates that both formal and informal vocational training positively influence women’s participation in gig jobs without relying on any digital platform. However, the impact of informal training is more pronounced.
Keywords: bivariantna Probit regresija; bivariate probit regression; casual wage labourer; formal vocational training; formalno poklicno usposabljanje; gig job; neplačano gospodinjsko delo; own-account worker; priložnostni nadomestni delavec; priložnostno delo; samozaposleni delavec; unpaid household job